Design and Experimental Evaluation o`f a PID Based Ship Rudder Control Prototype Referenced to SOLAS - Arif, Arif Rakhman Suharso; Ario Hendartono; Amthori, Amthori Anwar; Slamet Supriyadi (Advance Sustainable Science Engineering and Technology, 2026)
The Proportional–Integral–Derivative (PID)-based ship rudder control system is an effective method for maintaining a vessel’s heading automatically. This study aims to design and evaluate a ship rudder control prototype in accordance with SOLAS safety standards. The research method employed is Research and Development (R&D), which includes needs analysis, system design, prototype development, and model testing. The cargo ship prototype is equipped with an HMC5883L compass sensor, an Arduino microcontroller, and a servo motor as the rudder actuator. Data processing and PID algorithm implementation are carried out using Visual Basic software. The PID parameters used are Kp = 0.001, Ki = 0.001, and Kd = 0.2, obtained through a tuning process. Testing was conducted in a controlled pool under calm water conditions. The results show that the system achieves a steady-state condition in an average time of 21 seconds with minimal overshoot and small deviation from the setpoint, while complying with the SOLAS requirement of a maximum rudder angle of 35°.